Enhancing nutrient use efficiency of maize (Zea mays L.) from mixing urea with zeolite and peat soil water. - Omar, Latifah; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2011)
The use of urea as N fertilizer has increased globally but lack of efficiency due to loss through ammonia volatilization has become a subject of considerable recent attention. In line with this, a pot experiment was conducted to determine the effect of mixing urea with zeolite and peat soil water on: (1) uptake and use efficiency of N, P and K in maize cultivation, and (2) soil exchangeable ammonium, available nitrate, pH, exchangeable K, and available P contents. The treatments evaluated were: No fertilizer (T0), 2.02 g urea (T1), 2.02 g urea + 30 g zeolite + 7 L peat soil water (T2), 2.02 g urea + 40 g zeolite + 7 L peat soil water (T3), and 2.02 g urea + 7 L peat soil water (T4). The fertilizers of TSP and MOP were applied twice that is 10 and 28 days after planting for all the treatments except T0. The application of peat soil water, and zeolite with urea had significant effect on dry matter, N, P, K uptake and N, P, K use efficiency compared with urea without additives. The soil exchangeable ammonium, K, Ca, Mg, available P, and nitrate contents were significantly increased compared with urea without additives. Formation of ammonium and nitrate over ammonia were reflected by the mixtures of peat soil water, and zeolite, with urea. Amending urea with zeolite and peat soil water can reduce ammonia loss by encouraging formation of ammonium and nitrate over ammonia. In addition, the mixtures ensure N, P, K uptake and their use efficiency while at the same time rendering soil ammonium, K, Ca, Mg, P, and nitrate available for plant use.